Waste Analysis of Isolating Cook Production Processes Through Manufacturing and Ergonomic Lean Approaches (Case Study Pt Pindad (Persero) Bandung - Anggara, Surya Firman; Hermanto, Riko; Hermawan, Lasmana Yan; Chang, Young Hwan; Margana, Riki Ridwan (International Journal of Psychosocial Rehabilitation, 2026)
The company has a standard time in the production process, so delays are something that must be avoided. PT Pindad (Persero) is a manufacturing industry company that produces military and non-military products in Indonesia. The Isolating Cook product is a part of the Railway Air Brake System which is produced by PT Pindad (Persero) in the railway facilities department of the forging and railway division. The Isolating Cook production process has a one minutes delay for one product, so a waste analysis is needed to eliminate unnecessary activities so that the production process becomes smoother. This research uses ergo waste analysis method which is then approached through the REBA method as a recommendation for a better work posture. The results obtained from the initial research using the REBA method obtained a score of 4 to 6 which means it has a medium risk value and after the improvement is done, a score of 3 indicates a low risk in work posture. Based on the results of the study using the waste analysis method, the dominant waste is in the form of waste of motion. The results of improving work posture using the REBA method show the results of scores that are in the range of low risk, so that production operators avoid work risks that can hinder the production process. The application of work posture recommendations, 5S and proposed improvements that have been recommended in the Isolating Cook production process in the form of eliminating movements deemed as waste and also recommendations to regulate the placement of work tools so that they are easily accessible to workers as a cause of the emergence of wasteful movements, so that the production process it becomes faster or the actual time after repairing becomes balanced with the estimated time given.